MAKNA SAKRAMEN PERKAWINAN BAGI PASUTRI USIA MADYA - Marta Gimbut; Yuventius Fusi Nusantoro (Bahasa Indonesia, 2019)
Couples who have been married for six up to twenty five years cannot apart from obstacles which appear in their family life. Most of obstacles that they face are about economic problem, educational problem, divorce, having a secret affair, barren, being selfish, lacking of attention, disputing, and so on. These things cause a conflict in family. Besides, the married couples will find difficulty in understanding the true meaning of married sacrament. Every kind of effort has been done by them in order to keep their marriage in peace and harmony. To make it happen, they must love each other, be faithful, and honest. Moreveor, they must accept the strength and weakness of their partner and be grateful for everything they have. By being grateful, god will protect their marriage. Marriage is a thing which is given by god himself He is the only one who is able to unite two different people, man and woman, to form a new family. Based on the problem stated in this research, the aims of the research are describing the meaning of married sacreament, identifying the challenges that they face in understanding the meaning of married sacrament, and explaning their efforts in understanding the meaning of married sacrament.